Benefit payment costs of unemployment insurance modernization: Estimates based on Kentucky administrative data - Christopher J. O'Leary (W.E. Upjohn Institute for Employment Research, 2011)
The American Recovery and Reinvestment Act (ARRA) of 2009 provided financial incentives for UI modernization. The financial incentive is the state share of 7 billion available nationwide. States can receive one-third of their allocation by having an alternate base period (ABP) for monetary determination of UI eligibility that includes the most recently completed calendar quarter. States can receive the remaining two-thirds of their allocation for having two of four additional program features: 1) UI eligibility while seeking only part-time work, 2) UI eligibility after job separations due to harassment or compelling family reasons, 3) continuation of UI benefits for at least 26 additional weeks after exhaustion of regular benefits while in approved training, and 4) dependents' allowances of at least 15 per dependent up to 50. This paper presents estimates of the UI benefit payment costs of these five program changes based on data from the Commonwealth of Kentucky. To date 39 states have received modernization payments for having an ABP, and 32 states have received the remaining two-thirds of funds available. The numbers of states adopting each of these additional features are as follows: 25 for seeking part-time, 18 for family reasons, 14 for exhaustee benefits while in training, and 7 for dependents' allowances. Estimates of the UI benefit payment costs for these features, based on Kentucky data, suggest a pattern of states choosing UI modernization features to minimize the expected benefit payment costs. However, for states broadening UI eligibility through modernization, UI benefit payment costs will be higher for any given level of unemployment. Liberalized eligibility rules must be balanced by structural financing enhancements to ensure long-term fiscal stability of the system.
Keywords: J65; J68; H83; 330; unemployment insurance; UI; modernization; American Recovery and Reinvestment Act; benefit payments; Kentucky; administrative data; state expenditures